A Novel Strategy for Single-Session Ultrasound-Guided Radiofrequency Ablation of Large Benign Thyroid Nodules: A Pilot Cohort Study - Yao, Zhicheng; Wu, Tao; Zheng, Bowen; Tan, Lei; Lian, Yufan; Liu, Bo; Ren, Jie (Frontiers in Endocrinology, 2020)
Background: Ultrasound-guided radiofrequency ablation (RFA) of thyroid nodules (TNs) is a minimally invasive procedure that has been widely used to induce volume reduction in symptomatic solid benign TNs. The goal of this study was to investigate a novel therapeutic approach for single-session ablation of large thyroid nodules (LTNs, vol > 20 ml). Methods: We performed a pilot cohort study of 21 patients with symptomatic solid benign LTNs (vol > 20 ml), who accepted ultrasound-guided RFA treatment between September 2018 and November 2019. RFA was performed using an 18-gauge internally cooled electrode with ultrasonographic guidance in a single session combined with intraoperative hydrodissection and immediate contrast-enhanced ultrasound (CEUS) to optimize safety and efficacy. Nodule volume was evaluated before ablation and at 1, 3, and 6 months after initial ablation, and all patients were asked to assess the cosmetic score (from 1 to 4) and symptom score (from 0 to 10) before ablation and at every follow-up after ablation. Results: At the 6 month follow-up, there was significant nodule volume reduction, from 27.49 ml ± 7.9 (standard deviation) to 3.82 ml ± 5.02 (p = 0.001). Cosmetic signs (p = 0.001) and pressure symptoms (p = 0.001) were significantly improved. All patients underwent RFA without any major complications, and very few patients developed a change in voice (2/21). However, the changes subsided within 1 month. Almost half of the patients received an additional RFA (11/21) treatment to achieve complete ablation on the intraoperative immediate CEUS evaluation. Conclusion: RFA is effective for treating LTNs (vol > 20 ml) and controlling clinical symptoms with a low complication rate. Patients were satisfied with cosmetic sign and pressure symptom improvement. The intraoperative hydrodissection and immediate CEUS represent a novel therapeutic approach for single-session ablation of LTNs.